Natural Variation of Root Traits: From Development to Nutrient Uptake. Issue 2 (7th August 2014) - Ristova, Daniela; Busch, Wolfgang
Abstract : Natural variation of root growth informs on processes that govern root development, responses to nutrient availability, and ion uptake and homeostasis . Abstract: The root system has a crucial role for plant growth and productivity. Due to the challenges of heterogeneous soil environments, diverse environmental signals are integrated into root developmental decisions. While root growth and growth responses are genetically determined, there is substantial natural variation for these traits. Studying the genetic basis of the natural variation of root growth traits can not only shed light on their evolution and ecological relevance but also can be used to map the genes and their alleles responsible for the regulation of these traits. Analysis of root phenotypes has revealed growth strategies and root growth responses to a variety of environmental stimuli, as well as the extent of natural variation of a variety of root traits including ion content, cellular properties, and root system architectures. Linkage and association mapping approaches have uncovered causal genes underlying the variation of these traits.